Lesson Planning and Proactive Classroom Management Strategies for Teaching English at Tertiary Level in Pakistan - Ali, Ameer (Elsya : Journal of English Language Studies, 2021)
There is scarcity of research on classroom management and lesson planning at tertiary level, so the current research investigates these dimensions at tertiary level in Pakistan’s context. This research article is an investigative attempt of understanding lesson planning and proactive classroom management strategies for teaching English at tertiary level in Pakistan. In this regard, the current research analyses primary data collected from the research participants. Moreover, this research paper is qualitative, because it answers open-ended questions using cross-sectional survey as a data collection tool. The investigator has made use of purposive sampling for selecting research participants from different sections of Pakistan’s tertiary level education institutions. The researcher has also employed thematic analysis method to study the collected data. The study reveals that many teachers set objectives, such presentation stage, production stage, and practice stage while planning their lessons. Similarly, the teachers at tertiary level employ behaviour and discussion-based strategies to bring forth proactive classroom management. These findings contribute to the understanding of educationists and bring about further research work at tertiary level from different dimensions. Overall, this research contributes to the pool of knowledge as a qualitative attempt of studying pedagogical management and planning at tertiary level.